1998
DOI: 10.1034/j.1600-0501.1998.090104.x
|View full text |Cite
|
Sign up to set email alerts
|

Delayed immediate implants: alveolar bone chamzes durinrr the healing period

Abstract: Delaying the placement of immediate fixtures by 6-8 weeks after extraction of the natural dentition allows for the elimination of associated infective processes, the achievement of maximum osteoblastic activity that theoretically could help the osseointegration process and complete wound covering that simplifies the placement of grafts or membranes. This study examines the healing associated with 21 fixtures in 14 patients. The fixtures were placed into sockets 6-8 weeks after tooth extraction without the use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 0 publications
2
21
0
Order By: Relevance
“…In these studies, initial defect heights ranged from 2.4 to 8.4 mm. In contrast, percentage height reductions of over 85% were noted at implants placed using a 'delayedimmediate' protocol 4-6 weeks after extraction (Nir-Hadar et al 1998;Nemcovsky et al 2002). The enhanced result is likely to be because of the larger size of the initial defects in the current study sample (mean initial defect height of 9 mm).…”
Section: Discussionmentioning
confidence: 94%
“…In these studies, initial defect heights ranged from 2.4 to 8.4 mm. In contrast, percentage height reductions of over 85% were noted at implants placed using a 'delayedimmediate' protocol 4-6 weeks after extraction (Nir-Hadar et al 1998;Nemcovsky et al 2002). The enhanced result is likely to be because of the larger size of the initial defects in the current study sample (mean initial defect height of 9 mm).…”
Section: Discussionmentioning
confidence: 94%
“…Even more important is the need to maintain the marginal bone level and, consequently, the soft tissue level too, in the front areas of the arches where the aesthetics play a fundamental role. It has been demonstrated that the positioning of an implant in a fresh extraction site can prevent the resorption, especially on the buccal side where the bone is generally thinner 24–25 …”
Section: Discussionmentioning
confidence: 99%
“…Traditional protocols for restoring these sites rely on bone deposition to fill the extraction site before the implant is placed. 5,6 Hard and soft tissue grafting often is necessary to provide an ideal functional and esthetic restoration. Grafts compensate for the bone resorption that accompanies the natural healing process in an extraction socket.…”
Section: Socket Healingmentioning
confidence: 99%